2021
DOI: 10.3389/fimmu.2021.782780
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Mevalonic Aciduria Complicated by Acute Myeloid Leukemia After Hematopoietic Stem Cell Transplantation

Abstract: Mevalonic aciduria (MA) is the most severe clinical subtype of mevalonate kinase deficiency (MKD) caused by an inherited defect in the mevalonate pathway. The treatment of MKD focuses on the suppression of recurrent hyperinflammatory attacks using anti-inflammatory drugs. Recently, allogeneic hematopoietic stem cell transplantation (HCT) was shown to successfully ameliorate autoinflammatory attacks in patients with MKD. Here, we report a case of an infant who showed severe recurrent systemic inflammation and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…According to previous reports, hematopoietic stem cell transplantation is also an effective method for treating severe HIDS [ 6 , 7 ]. However, severe symptoms related to transplantation may be life-threatening [ 37 ]. Moreover, there may be recurrence after transplantation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, hematopoietic stem cell transplantation is also an effective method for treating severe HIDS [ 6 , 7 ]. However, severe symptoms related to transplantation may be life-threatening [ 37 ]. Moreover, there may be recurrence after transplantation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the aforementioned genes, causing the downregulation of the corresponding protein expression, have been reported to produce mevalonate deficiency, resulting in abnormal apoptosis in the keratinocytes. MVK deficiency is an autosomal recessively inherited disease that has three different clinical presentations: DSAP, hyper IgD syndrome and mevalonic aciduria [78,96,[100][101][102][103][104]. It was reported that the DSAP severity closely correlates with the MVK level [96,105].…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%
“…Analysis of genomic variants of the mevalonate pathway in porokeratosis showed that the most frequent mutations found in DSAP were in the MVK (26/130 patients) and MVD (56/130 patients) [15]. At least MVK deficiency is an autosomal recessively inherited disease that has three different clinical presentations: DSAP, hyper IgD syndrome and mevalonic aciduria [78,96,[100][101][102][103][104]. It was reported that the DSAP severity closely correlates with the MVK level [96,105].…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%